PERANCANGAN SISTEM STOCK OPNAME BERBASIS WEB PADA KAFE KOPKIT - Zahelna Azzahra, Karisa; Irfan, Dedy; Dwinggo Samala, Agariadne; Asmara, Delvi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Stock opname activities at Kafe Kopkit, a food and beverage business operating eight outlets, are still recorded manually using paper-based logbooks, which causes discrepancies between physical and system stock, delays in reporting, and difficulty for management in monitoring the completion of stock opname across outlets, particularly because most outlets operate for twenty-four hours. This study aims to design and build an integrated web-based stock opname information system that supports real-time monitoring and provides an objective performance ranking of outlets to support managerial decision making. The system was developed using the Prototype method, which allows iterative refinement based on feedback from five user roles (Owner, Operational Management, Outlet Management, Kitchen, and Bar), and was verified functionally using Black Box Testing. To rank outlet performance, the system implements the Simple Additive Weighting method using four criteria: stock discrepancy rate, stock opname completion percentage, stock opname frequency, and completion timeliness. Black box testing on twelve functional scenarios produced a one hundred percent valid result, and the Simple Additive Weighting calculation successfully differentiated and ranked eight simulated outlets consistently with their input performance data. The system is expected to reduce recording errors, accelerate cross-outlet monitoring, and provide a transparent, data-driven basis for evaluating outlet performance.